Occurrence of mobulid rays in Northwest Madagascar - Stella Diamant; Caterina Bosio; Joshua Rambahiniarison; Chris Scarffe; Michel Strogoff; Jeremy J. Kiszka; Rhett Bennett; Tanguy Guillemain d’Echon; Elina Sourisseau; Léonce C. M. Fidiarisandratra; Salvatore Cerchio; Stephanie Venables; et al. (Environmental Biology of Fishes, 2025)
The waters around Nosy Be in northwest Madagascar are well-known for the occurrence of large planktivores, such as whale sharks ( Rhincodon typus ) and Omura’s whales ( Balaenoptera omurai ). Between 2016 and 2022, sighting data on mobulid rays were opportunistically collected during tourism activities. Additional sources, including citizen science submissions, tourism operator reports, and social media records, were used to compile sightings of three mobulid ray species. A total of 255 encounters were documented, with Mobula mobular ( n = 165) being the most common, followed by M. birostris ( n = 60) and M. kuhlii ( n = 30). Notably, the absence of confirmed M. alfredi records since 2015 suggests a potential local decline. This study highlights Nosy Be as a habitat for mobulid rays and emphasises the necessity for further species monitoring, ongoing identification of potential threats, and management initiatives aiming at reducing mortality from gillnet fishing.